Seroprevalence and B1 gene Phylogeny of Toxoplasma gondii of Dogs and Cats in Republic of Korea - Park, Yeojin; Noh, Jinhyeong; Seo, Hyun-Ji; Kim, Keun-Ho; Min, Subin; Yoo, Mi-Sun; Yun, Bo-Ram; Kim, Jong-Ho; Choi, Eun-Jin; Cheon, Doo-Sung; Hong, Sung-Jong; Yoon, Soon-Seek; et al. (Korean journal of parasitology, 2020)
The outbreak of human toxoplasmosis can be attributed to ingestion of food contaminated with Toxoplasma gondii. Toxoplasmosis recently increased in domestic and stray dogs and cats. It prompted studies on the zoonotic infectious diseases transmitted via these animals. Sero- and antigen prevalences of T. gondii in dogs and cats were surveyed using ELISA and PCR, and B1 gene phylogeny was analyzed in this study. Toxoplasmosis antibodies were measured on sera of 403 stray cats, 947 stray dogs, 909 domestic cats, and 2,412 domestic dogs collected at nationwide regions, Korea from 2017 to 2019. In addition, whole blood, feces, and tissue samples were also collected from stray cats (1,392), stray dogs (686), domestic cats (3,040), and domestic dogs (1,974), and T. gondii-specific B1 gene PCR was performed. Antibody prevalence of stray cats, stray dogs, domestic cats, and domestic dogs were 14.1%, 5.6%, 2.3%, and 0.04%, respectively. Antigen prevalence of these animals was 0.5%, 0.2%, 0.1%, and 0.4%, respectively. Stray cats revealed the highest infection rate of toxoplasmosis, followed by stray dogs, domestic cats, and domestic dogs. B1 gene positives were 5 of stray cats, and identified to high/moderate pathogenic Type I/III group. These findings enforce that preventive hygienic measure should be strengthened at One Health level in dogs and cats, domestic and stray, to minimize human toxoplasmosis infections.